Feminine Writing: Text as Dolls, Drag and Ventriloquism. Issue 2 (13th February 2015) - Rippin, Ann
Abstract : This article provides a case study of feminine writing, including the production of text in the form of a series of three dolls. It seeks to broaden ideas about what is acceptable as research including notions of 'data' and representation. To do this it employs the written word, but includes fiction, asking if this is 'fictional truth'. The article considers the position of women in organizations through the creation of three rag dolls which represent the author's experience of women in organization. This is followed by three fictional 'interviews' with the dolls in which they describe their experiences of organizing and being organized in a gendered world. The paper ends with a reflection on the usefulness and validity of this arts methodology and outlines the feminist critique of organizations and organizing that the method reveals. I describe this as feminine writing because it troubles or queers conventional academic writing by producing a text (the dolls and the fiction) which is rich in embodiment and affect, and which has a feminist project: that of exposing the myriad ways in which women and organizations may be seen (and are seen in this article) as incompatible.